Shamanic trance in modern Kabbalah - Garb, Yehonatan 1967- (Chicago The University of Chicago Press, 2011)
Bringing to light a hidden chapter in the history of modern Judaism, Shamanic Trance in Modern Kabbalah explores the shamanic dimensions of Jewish mysticism. Jonathan Garb integrates methods and models from the social sciences, comparative religion, and Jewish studies to offer a fresh view of the early modern kabbalists and their social and psychological contexts. Through close readings of numerous texts--some translated here for the first time--Garb draws a more complete picture of the kabbalists than previous depictions, revealing them to be as concerned with deeper states of consciousness as they were with study and ritual
Includes bibliographical references (pages 231-260) and index. - Print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Cabala; Shamanism; Religion; RELIGION ; Judaism ; Kabbalah & Mysticism; Electronic books